An evolutionary perspective on leaf economics: phylogenetics of leaf mass per area in vascular plants. Issue 14 (1st July 2014) - Flores, Olivier; Garnier, Eric; Wright, Ian J.; Reich, Peter B.; Pierce, Simon; Dìaz, Sandra; Pakeman, Robin J.; Rusch, Graciela M.; Bernard‐Verdier, Maud; Testi, Baptiste; Bakker, Jan P.; Bekker, Renée M.; et al.
Abstract In plant leaves, resource use follows a trade‐off between rapid resource capture and conservative storage. This "worldwide leaf economics spectrum" consists of a suite of intercorrelated leaf traits, among which leaf mass per area, LMA, is one of the most fundamental as it indicates the cost of leaf construction and light‐interception borne by plants. We conducted a broad‐scale analysis of the evolutionary history of LMA across a large dataset of 5401 vascular plant species. The phylogenetic signal in LMA displayed low but significant conservatism, that is, leaf economics tended to be more similar among close relatives than expected by chance alone. Models of trait evolution indicated that LMA evolved under weak stabilizing selection. Moreover, results suggest that different optimal phenotypes evolved among large clades within which extremes tended to be selected against. Conservatism in LMA was strongly related to growth form, as were selection intensity and phenotypic evolutionary rates: woody plants showed higher conservatism in relation to stronger stabilizing selection and lower evolutionary rates compared to herbaceous taxa. The evolutionary history of LMA thus paints different evolutionary trajectories of vascular plant species across clades, revealing the coordination of leaf trait evolution with growth forms in response to varying selection regimes.